Service Quality as a Strategic Driver of External Customer Satisfaction: Evidence from a Semi-International School in Indonesia - Paulus Sunarjo; Chasan Ma'ruf; Yolanda Tasyha (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This research aims at disclosing deeply and describing things that are enable the customers to feel satisfied with the education services provided by Sekolah Highscope Indonesia. In analyzing the data, three main theories were chosen, namely Service Dominant Logic, Total Quality Management, and Factors of Customer Satisfaction. The research methodology chosen was Qualitative, in which interviews, participatory observation, and document study were done. The important findings of this research are: (1) the English language competence of Sekolah Highscope Indonesia graduates, (2) the modern and unique education concept, (3) the graduates (alumni) who are competitive globally, (4) the responsiveness of the school management and teachers when there is complaint or concern, (5) the core values (respect, responsibility, excellence, and integrity) developed and internalized for the students, (6) parents regarded as partners, and (7) the teachers’ high competence. Based on these study results, practical recommendations can be given to SHI, i.e. these very good things should be maintained and implemented consistently. As for social science recommendations, if possible the research in the future should use quantitative methodology, so that the results will probably reflect customer’s satisfaction better since quantitative research use more research population sampling